The split in the ancient cold front in the Perseus cluster. (April 2018) - Walker, Stephen; ZuHone, John; Fabian, Andy; Sanders, Jeremy
Abstract Sloshing cold fronts in clusters, produced as the dense cluster core moves around in the cluster potential in response to in-falling subgroups, provide a powerful probe of the physics of the intracluster medium and the magnetic fields permeating it1, 2 . These sharp discontinuities in density and temperature rise gradually outwards with age in a characteristic spiral pattern, embedding into the intracluster medium a record of the minor merging activity of clusters: the further from the cluster centre a cold front is, the older it is. Recently, it was discovered that these cold fronts can survive out to extremely large radii in the Perseus cluster3 . Here, we report on high-spatial-resolution Chandra observations of the large-scale cold front in Perseus. We find that rather than broadening through diffusion, the cold front remains extremely sharp (consistent with abrupt jumps in density) and instead is split into two sharp edges. These results show that magnetic draping can suppress diffusion for vast periods of time—around ~5 Gyr—even as the cold front expands out to nearly half the cluster virial radius. Sloshing cold fronts in galaxy clusters—sharp jumps in density and temperature—retain a long-lived history of the motion of the cluster core. Chandra observations show that the cold front in Perseus is extremely sharp and is split into two edges.